The symbiosis in Electra of Euripides: Elaboration of a Didactic - Christou, Maria; Logothetou, Martha; Manthou, Chrysa (Adult Education Critical Issues, 2025)
In this article, it is attempted to highlight, the perennial issue of symbiosis with a critical analysis of its patterns, as they emerge in the tragedy "Electra" by Euripides and by utilizing works of art, through a didactic intervention in the Self-Education Group of the H.A.E.A. Part of the "Transformative Learning through Aesthetic Experience" method and art processing techniques are used aiming to enhance the emergence of emotions, critical reflection and self-reflection of the participants when approaching the tragedy, while emphasizing the importance of its utilization in the educational frame.